Understanding The Differences In Second Language Acquisition Processess On Children And Adults - Sujono Sujono (Dharma Pendidikan, 2020)
Second language acquisition (SLA) is the process of learning another language after the native language has been learned. The children in SLA is divided in to two categories children under seven and children between 7-12. What is called adult here is people above 12 years old. In SLA children and adult differ in three categories: psychology, social context, and other psychological variables. On psychological factor children are high on induction, memory, motor skill, and low in explication. While on the social context, children are high in natural context but low in classroom context. On the other hand, adults are high on induction, explication, and classroom situation. But they low or medium in memory, motor skill, and in natural context. In some other factor children is best at ESL (English as Second Language) situation and adult best at EFL (English as Foreign Language) situation. In SLA the adult is high in motivation and attitude while the children are the converse.